Comparison of Test Methods for Determining the Tensile Strength of Soil and Weak Rocks - Wang, Rong; Li, Yanrong; Lv, Dongdong; Zhao, Weichao; Zhang, Chaobo; Zachert, Hauke; Eichhoff, Gerald; Beroya-Eitner, Mary Antonette (Frontiers in Earth Science, 2022)
Tensile strength is a key parameter governing tensile cracking and subsequent failure of soil or rock mass. Existing methods for measuring tensile strength are mainly designed for hard materials and come with inherent problems. As such, they are continuously being adapted and improved by the scientific community. In line with this effort, we recently developed two new tensile test methods for application to soil and weak rocks, namely, the inner hole fracturing test (IHFT) and horizontal compression test (HCT). In this study, we compared the performance of these newly developed methods and the three most commonly used approaches for tensile strength determination, namely, the uniaxial direct tensile test (UDTT), Brazilian test (BT) and three-point bending test (TPBT). Results show that IHFT and HCT exhibit distinct advantages over the three conventional methods when testing soil and weak rocks: first, IHFT and HCT can overcome the eccentric force problem that is a main challenge in UDTT and BT, and second, results obtained from these tests are highly reproducible and stable. Between IHFT and HCT, the latter is found more suitable for routine laboratory testing because of simpler and easier procedure, more stable and reliable results and uniform stress distribution within specimens.